Análise morfotectônica e morfoestrutural no controle de erosões hídricas lineares na região de Marília (SP) - Morinaga, Márcia Sayuri [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The west of the state of São Paulo is known by its strong agricultural vocation and by the erosion problems. The natural conditions and the occupation dynamic were propitious to the emergence of this kind of environmental degradation in the soil, resulting in loss of usable area, siltation of water bodies and demands on infrastructure. Linear hydraulic erosion, such as ravines and gullies, have as forming factors the climate, soil, land slope and the use. Many authors relate the rock structural conditions as one of the conditions of the emergence and development of this kind of erosion. To enlarge the knowledge about this subject, the present work aimed an analysis of the brittle and ductile geologic deformations and its relations to the accelerated linear hydraulic erosion in the region of Marília (SP), through the interpretation of remote sensing images. The study area comprises the latitudes 22°00’S and 22°15’S and the longitudes 49°45’W and 50°15’W and has one of its main characteristics the presence of the Marília Plateau, a plateau with festooned slopes which stands out in the landscape, composed by the carbonate sandstone from the Marília Formation (Bauru Group). Structural lineaments, joint traces and structural highs and lows where, therefore, mapped. The two first linear features were analyzed in relation to its frequencies and directions; whereas the dome and depressive structures were related to its topographic positioning. To enlarge the knowledge of the study area, it was performed physiographic analysis and of weathering alteration covers by satellite image interpretation, field works and bibliographic queries. Finally, these information were related to the development of the linear erosions, features that were identified from aerial photographs and proved in field. Among the results, it was observed that the structure frequencies of brittle deformation did not present correlation with the development of the...

O oeste do Estado de São Paulo é conhecido pela sua forte vocação agrícola e pelos problemas com erosão. As condições naturais e a dinâmica de ocupação foram propícias para o surgimento deste tipo de degradação ambiental no solo, resultando em perda de área útil, assoreamento de corpos d’água e demandas na infraestrutura. Erosões hídricas lineares, como ravinas e voçorocas, têm como fatores de formação o clima, solo, declividade do terreno e o uso. Muitos autores relacionam as condições estruturais das rochas como um dos condicionantes do surgimento e desenvolvimento deste tipo de erosão. Para ampliar o conhecimento sobre este assunto, o presente trabalho objetivou uma análise das deformações geológicas rúpteis e dúcteis, e suas relações com as erosões hídricas lineares aceleradas da região de Marília (SP), através de interpretação de imagens de sensores remotos. A área de estudo compreende as latitudes 22º00’S e 22º15’S e as longitudes 49º45’W e 50º15’W e tem uma de suas principais características a presença do Planalto de Marília, um planalto com encostas festonadas que se destaca na paisagem, composta pelo arenito carbonático da Formação Marília (Grupo Bauru). Foram, então, cartografados: lineamentos estruturais, traços de junta e altos e baixos estruturais. As duas primeiras feições lineares foram analisadas com relação às suas frequências e direções; já as estruturas dômicas e depressivas foram relacionadas ao seu posicionamento topográfico. Para ampliar o conhecimento da área de estudo, foram realizadas análises fisiográfica e de coberturas de alteração intempérica (CAI) por interpretação de imagem de satélite, trabalhos de campo e consultas bibliográficas. Finalmente, essas informações foram relacionadas ao desenvolvimento das erosões lineares, feições estas identificadas a partir de fotografias aéreas e comprovadas em campo. Dentre os resultados...
Keywords: Erosion; Erosão; Solos - Deformação; Geologia estrutural; Geomorfologia; Marilia (SP)